Perceptions of instructional leadership behaviour of school principals, Sarawak - Lindong, Lambat (1998)
The study examined the instructional leadership behaviour of secondary school principals in Sarawak from the perspectives of principals themselves and their teachers. The primary focus of the study was on identifying, describing and analyzing the perceptions of principals and teachers regarding principal's job behavior in instructional leadership. Specifically, the study sought to describe and compare the perceived actual and expected behavior of principals instructional leadership; to determine the extent to which principals were expected to perform, and had actually performed, their role as instructional leaders; and to describe constraining factors that were perceived to have hindered the instructional leadership effectiveness of principals, as well as to identify beneficial improvement measures. Nine research questions were formulated to guide the study.